2010
DOI: 10.1063/1.3486467
|View full text |Cite
|
Sign up to set email alerts
|

Peak effect of flux pinning in Sc5Ir4Si10 superconductors

Abstract: Magnetic hysteresis loops ͑MHLs͒ have been comparatively measured on both textured and single crystalline Sc 5 Ir 4 Si 10 superconductors. Critical current densities and flux pinning forces are calculated from MHLs by Bean model. Three kinds of peaks of the flux pinning force are found at low fields near zero, intermediated fields, and high fields near the upper critical field, respectively. The characters and origins of these peaks are studied in detail.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…5(b). These narrow peaks at low fields have also been seen in our previous work on Sc5Ir4Si10, [33] where it was ascribed to the surface barrier. In InTe0.9Se0.1, the very asymmetric MHLs shown in Fig.…”
supporting
confidence: 82%
“…5(b). These narrow peaks at low fields have also been seen in our previous work on Sc5Ir4Si10, [33] where it was ascribed to the surface barrier. In InTe0.9Se0.1, the very asymmetric MHLs shown in Fig.…”
supporting
confidence: 82%
“…Those h locations are almost unchanged with temperatures, and only the peak intensity becomes different. This phenomenon can be found in Sc 5 Ir 4 Si 10 [36] and FeSe 0.91 S 0.09 [37]. Here, the f p peak position shifts gradually with temperature in Fe 1+y Te 0.6 Se 0.4 , excluding the possibility of different pinning mechanisms.…”
Section: Non-scaling Behavior Of Fp Along C Axismentioning
confidence: 54%
“…Detailed structure and composition analyses have been reported in our previous publication. 13) Temperature dependences of zero-field-cooled (ZFC) and field-cooled based on the BCS theory…”
Section: Resultsmentioning
confidence: 99%
“…25,26) In the case of anisotropic s-wave, Nakai et al 27) theoretically revealed that ( ) H γ shows a crossover from H linear dependence at low field to H at high fields. Thus we replot the 13) together with that from Sc 5 Ir 4 Si 10 single crystal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation